Changing resistant audience attitudes using social judgment theory's "anchor" point perspectives. Issue 2 (3rd April 2017) - Ramos Salazar, Leslie
Abstract : Courses: Public Speaking, Business and Professional Communication, Persuasion, or any other skill-based oral communication course. Objectives: Students will practice the development and demonstration of persuasive arguments in this single-class social judgment theory activity to improve their ability to change resistant audience attitudes.